Internalisasi Hadis Tarbawi dalam Media Sosial “Omar Hana” Sebagai Model Pendidikan Anak Islam di Indonesia - Dwi Aryanti, Savira; Ubaidillah (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2024)
The development of hadith studies continues to experience dynamism, not only sanad and matan, but has developed into various trends of study from text to social media. Various innovations and creations of hadith literature began to emerge, such as Omar Hana's Islamic animated content. This research focuses on the internalization of hadith in Omar Hana's Islamic animation content as a way of Islamic child education, with the formulation of problems that include the interpretation of hadith in Omar Hana's Islamic animation content, aesthetic value, and its positive implications. The goal is to reveal the form of hadith reception in Omar Hana's Islamic animation in internalizing the Prophet's hadith as Islamic child education. The method used in the research is library research with the theory of reception introduced by Ahmad Rafiq, which refers to three steps, namely exegesis, aesthetic, and functional. This study found the first fact, that the hadith in Omar Hana's Islamic animation content is conveyed with song lyrics accompanied by typical children's backsound and displays the hadith translation at the end of the video. Second, the reception of the hadith text in the content of Omar and Hana uses aesthetic reception of hadith in the form of digitally animated visualization. While the hadith used is themed on daily practices from waking up to sleeping again by taking pieces of the matan of the hadith without including the sanad and the quality of the hadith. Functionally, the value of the teaching can be a medium for children's moral education although it is not representative enough in terms of the scientific discourse of hadith by mentioning the position of the status of hadith.